Hukum Melemahkan/Mematikan Syahwat pada Penderita Down Syndrome Perspektif Hukum Islam: The Law on Weakening/Terminating Sexual Desire in Individuals with Down Syndrome: an Islamic Legal Perspective - Sartini Lambajo; Siti Sa’dianti; Haryaty (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
Individuals with Down syndrome experience normal biological development, including the emergence of sexual urges (syahwat). However, this is often accompanied by insufficient mental and social capacity to manage these urges responsibly. This condition can result in the risk of sexual behavior deviation or becoming victims of sexual violence. This study aims to analyze the concept and Islamic law regarding the suppression or control of syahwat in individuals with Down syndrome. This research is a library research study employing a normative and psychological approach. Data is collected from primary and secondary literature, such as fiqh books, tafsir, journals, and academic articles, and analyzed descriptively-qualitatively. The findings indicate that methods to control syahwat include fasting, istimnā’ (self-stimulation), and castration (both physical and chemical). Islamic law encourages fasting as a permissible and beneficial method. In contrast, opinions regarding istimnā’ and castration differ among scholars. Physical castration is categorically prohibited, while chemical castration is allowed only in emergency situations and with strict considerations of benefits (maslahah) and harms (mafsadah). The implications of this study emphasize the importance of a preventive and educational approach based on religion, as well as family support, in managing the sexual urges of individuals with Down syndrome, rather than coercive methods that may violate the principles of maqāṣid al-Syarī‘ah.